THE EFFECT OF LEVERAGE, COMPANY SIZE AND PROFITABILITY ON DIVIDEND PAYMENTS - Aletha Kevina Putri Purwantoro; Menik Indrati (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2026)
This study aims to examine the effect of leverage, firm size, and profitability on dividend payments. The population consists of 75 energy sector companies during the 2021–2023 period. The sample was determined using a purposive sampling technique based on specific criteria, resulting in 23 companies with a total of 69 observations. The research employed a quantitative method analyzed using panel data regression with EViews 13 software. Model selection was conducted through the Chow test, Hausman test, and Lagrange Multiplier (LM) test to determine the best model. Subsequently, classical assumption tests were performed, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, followed by hypothesis testing. The results indicate that firm size and profitability have a positive effect on dividend payments. Meanwhile, leverage has no effect on dividend payments. These findings suggest that a company’s ability to generate profits and its scale can be determining factors in dividend payments, whereas leverage has not yet become a determining factor in dividend payments.